TRIM25 facilitates ferroptosis in ovarian cancer through promoting PIEZO1 K63-linked ubiquitination and degradation - Ya Li; Fei Zhou; Zhengmei Xu (Translational Oncology)
Background: Ovarian cancer represents a significant threat to women's health. and ferroptosis is recognized as a potential natural inhibitor in cancer therapy, the regulatory mechanism of TRIM25 in ovarian cancer and its potential for regulating ferroptosis as a treatment remain unclear. Methods: The role of TRIM25 in ovarian cancer was examined through functional gain- and loss-of-function assays both in vitro and in vivo, while its target genes were identified. The stability and ubiquitination sites of PIEZO1 were analyzed using protein docking and ubiquitination experiments. Results: TRIM25 is highly expressed in ovarian cancer and promotes the growth and metastasis of ovarian cancer cells both in vivo and in vitro. Mechanistically, it facilitates PIEZO1 degradation through ubiquitination-dependent proteasome activity, inhibits ferroptosis, and stimulates ovarian cancer cell growth. Conclusion: Our study clearly shows that TRIM25 stimulates ovarian cancer by inducing K63-linked ubiquitination of PIEZO1, which suppresses ferroptosis and promotes excessive proliferation of ovarian cancer cells. Further research identified the ubiquitination modification site on PIEZO1, providing insights for ovarian cancer treatment.